Variations in the Suspended Sediment Concentration in Mountain-Type Rivers Flowing Into the Sea in the Past 60 years—Taking Nanliu River in Beibu Gulf as an Example - Li, Shushi; Yang, Xialing; Huang, Hu; Liang, Xixing; Wang, Riming; Feng, Bingbin (Frontiers in Earth Science, 2022)
Small and medium rivers entering the sea in mountainous areas exhibit the characteristics of both mountains and streams, and the suspended sediment concentration (SSC) greatly contributes to the formation and evolution of deltas. However, scholars rarely give attention to the factors influencing changes in the suspended sediment concentration in small- and medium-sized mountainous rivers, and few studies have examined SSC changes in small- and medium-sized mountainous rivers. Here, based on daily SSC and flow data obtained at the Bobai Station and Changle Station, the percentile method and regression analysis method are employed to analyse the changes in SSC from the Nanliu River to the Beibu Gulf and possible influencing factors. The main research results indicate that (1) the SSC in river water bodies from 1965 to 2020 generally reveals a downwards trend, with significant annual variations. Specifically, the overall trend can be divided into three stages: (i) the SSC is the highest from 1965 to 1971, and the mean yearly SSC reaches 0.25 kg/m3; (ii) the SSC is relatively high from 1972 to 2006, and the mean yearly SSC reaches 0.16 kg/m3; and (iii) the SSC is the lowest from 2007 to 2020, and the mean yearly SSC reaches 0.11 kg/m3. (2) High values of the SSC are mainly concentrated in the flood season, and low SSC values mostly occur in the dry season. The monthly average SSC in the flood season from April to September and the dry season from October to March exhibits the characteristics of a decrease in the flood season and an increase in the dry season. Moreover, the peak SSC value in the watershed obviously occurs out of sync with the peak flow value. Generally, the former precedes the latter. (3) The curve of the flow rate-sediment ratio is an irregular clockwise rhombus. Moreover, the impact of tropical cyclones, land cover changes, regional GDP per capita, water consumption, and engineering construction are crucial reasons for the observed variations in the SSC in the Nanliu River Basin.